Four distinct patterns of anterior cruciate ligament injury in women`s professional football (soccer): a systematic video analysis of 37 match injuries - Achenbach, L.; Bloch, H.; Klein, C.; Damm, T.; Obinger, M.; Rudert, M.; Werner, K.; Szymski, D. (British Journal of Sports Medicine, 2024)
Background To identify mechanisms and patterns of anterior cruciate ligament (ACL) injury in adult women`s professional football by means of video match analysis.